2021
DOI: 10.3390/su13020445
|View full text |Cite
|
Sign up to set email alerts
|

An Exploration of the Critical Risk Factors in Sustainable Telecom Services: An Analysis of Indian Telecom Industries

Abstract: Different sources of risk factors can occur in sustainable supply chain management due to its complex nature. The telecommunication service firm cannot implement multiple improvement practices altogether to overcome the risk factors with limited resources. The industries should evaluate the relationship between risk factors and explore the determinants of improvement measures. The purpose of the present study is to identify and analyze critical risk factors (CRFs) for enhancing sustainable supply chain managem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 110 publications
0
10
0
Order By: Relevance
“…Rathore et al ( 2021) identified 15 associated safety risk factors using FDM to achieve a safe working environment in the healthcare system [158]. In sustainable supply chain management, Chen et al ( 2021) identified nine key risk factors using FDM as determinants of the case firm's improvement measures [159]. This study adopted an FDM to screen key SSCRs and agility criteria.…”
Section: Fuzzy Delphi Methodsmentioning
confidence: 99%
“…Rathore et al ( 2021) identified 15 associated safety risk factors using FDM to achieve a safe working environment in the healthcare system [158]. In sustainable supply chain management, Chen et al ( 2021) identified nine key risk factors using FDM as determinants of the case firm's improvement measures [159]. This study adopted an FDM to screen key SSCRs and agility criteria.…”
Section: Fuzzy Delphi Methodsmentioning
confidence: 99%
“…The research used qualitative information in the form of expert opinion and converting it into numerical form, shortlisting 25 essential factors out of 58. Another research evaluated risks in telecommunication industry of India, identifying most important risks via literature review and FDM, whereas Interpretive Structural Modelling (ISM) was used in combination with FDM to analysis the interrelationship among critical risks [ 102 ]. FDM has also been used in the construction industry perspective, a study highlighted major risks arising on construction sites using FDM in combination with DEMATEL to examine cause and effect of risk factors [ 103 ].…”
Section: Methodsmentioning
confidence: 99%
“…https://doi.org/10.31881/TLR.2022.40 Economic, social, and environmental concerns for human development are some of the components of sustainable development that have an impact on the supply chain and long-term business plans. To boost overall performance and obtain a competitive advantage in the rising market, industries have been urged to adopt sustainable practices in their supply chain operations by creative market, government laws, and growing awareness [9]. Figure 1 indicates the three spheres of sustainability.…”
Section: Introductionmentioning
confidence: 99%